2016
DOI: 10.1007/s13593-016-0366-x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation tillage increases soil bacterial diversity in the dryland of northern China

Abstract: Agricultural practices change soil's physical and chemical properties, therefore modifying soil microbial communities. Conservation tillage is widely used to improve the soil texture and nutrient status in the dryland regions of northern China. However, little is known about the influence of soil properties on microbes, in particular on the effect of conservation tillage on soil bacterial communities. Here, we studied the effect of a 5-year tillage treatment on soil properties and soil bacterial communities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
66
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(80 citation statements)
references
References 30 publications
13
66
1
Order By: Relevance
“…Conservation tillage has been linked to increases in overall diversity (see e.g. [ 14 , 21 , 63 , 69 , 70 ]) likely related to the preservation of microhabitats [ 62 , 63 ]. Consistent with prior studies, we observed a significant increase in the Shannon diversity index under no till treatment ( Fig 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservation tillage has been linked to increases in overall diversity (see e.g. [ 14 , 21 , 63 , 69 , 70 ]) likely related to the preservation of microhabitats [ 62 , 63 ]. Consistent with prior studies, we observed a significant increase in the Shannon diversity index under no till treatment ( Fig 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, decomposition of cover crops must be rapid enough to allow timely planting of the following crop [ 1 , 12 ]. No-till farming can reduce costs by reducing the use of heavy and expensive equipment, and can increase soil aggregation, SOM in the surface layer, water infiltration, water holding capacity, and reduce erosion [ 11 , 12 , 13 , 14 ]. On the other hand, no-till fields require closer monitoring, increased herbicide use for weed management, specialized equipment for planting new crops in surface residue, and may lead to reduced yields [ 1 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of our experiment are in line with the results of studies presented in reference publications. Wang et al [27] observed that the counts of Firmicutes and Proteobacteria in simplified tillage technologies were larger than in conventional tillage cultivation. Navarro-Noya et al [26] observed similar dependencies.…”
Section: Influence Of Various Cultivation Methods On Taxonomic Distrimentioning
confidence: 99%
“…The repeated tillage practices under CC may also affect their abundance and functioning in the agricultural soils [162]. Moreover, it is also commonly perceived that conventional CC practices decrease the biodiversity of soil earthworms more than conservation cropping practices [163,164]. Another study also reported that continuous cropping of cotton reduced the abundance of soil earthworms; among these, the abundance of Diplocardia caroliniana and Diplocardia caroliniana decreased up to 55-68%, and 88%, respectively [59].…”
Section: Soil Earthwormsmentioning
confidence: 99%